STATUS OF HEAVY METAL POLLUTION WITHIN SEDIMENT IN MANGROVE FOREST OF SEMARANG CITY AND DEMAK MUNICIPAL COASTAL AREA - Hastuti, Endah Dwi (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
Heavy metal pollution in Semarang City and Demak Municipal are increasing as the increase of industrial activity at both location. This research aimed to study the difference of heavy metal concentration in sediment, and to study the level of heavy metal pollution within mangrove area of Semarang City and Demak Municipal coastal areas. This research was conducted through sampling and laboratory analysis. At each location, 3 stations was occupied with 3 sampling points at each stations. Sampling was conducted for sediment within mangrove area at both location, while laboratory analysis was conducted in Laboratory of Analytical Chemistry, Chemistry Major, Faculty of Science and Mathematics Diponegoro University. Heavy metals in sediment observed in this research was Co, Cu, Cr, Pb, Zn, Ni, Fe, Mn and Mg. The result showed that heavy metal concentration in sediment on both location was quiet high. Sequentially, the highest to lowest concentration of heavy metal was Fe > Zn > Mn > Mg > Ni > Cu > Cr > Co > Pb at Semarang City and Fe > Mn > Mg > Zn > Ni > Pb > Cu > Co > Cr at Demak Municipal. Heavy metal concentration of sediment for Co, Cu, Cr, Zn and Ni are significantly different between Semarang City and Demak Municipal area. Heavy metal in sediment for Zn, Ni, Fe and Mn at both location had exceeded the recommended limit by ANZECC/ARMCANZ and ISQG. Keywords: heavy metal, mangrove, pollution state, sediment